Enzymatic Hydrolysis And Yeast Fermentation Of Okara - Ramli, Saadiah (Universiti Sains Malaysia, 2020)
The production of soybean-based product results in an insoluble residue called okara. This by-product that rich in protein, fat, and fiber nowadays was discarded as an agro-waste due to its poor properties such as easily putrefy and has high content of insoluble dietary fiber. To overcome this problem, a valorization of okara by the biological treatment could become one of the promising approaches to improve the nutritional value of okara. The objectives of this study were to determine optimum enzymatic hydrolysis condition on the release of total sugar by Viscozyme L and investigate the total protein content of okara after fermentation by Saccharomyces cerevisiae.